Humidity response type vapor phase corrosion inhibitor loaded hydrogel microspheres for copper metal as well as preparation method and application of humidity response type vapor phase corrosion inhibitor loaded hydrogel microspheres
By preparing porous hydrogel microspheres loaded with vapor-phase corrosion inhibitors, and utilizing the humidity responsiveness of chitosan and polyvinyl alcohol, the controlled release of the corrosion inhibitors on the copper surface was achieved. This solved the problem of excessively rapid volatilization rate of traditional corrosion inhibitors under high temperature and high humidity conditions, and improved the anti-corrosion effect of copper alloys.
Patent Information
- Application Number
- CN202511164914.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-20
- Publication Date
- 2025-11-28
AI Technical Summary
Traditional vapor phase corrosion inhibitors evaporate too quickly in high temperature and high humidity environments, resulting in a shortened protection cycle and making it difficult to effectively protect copper and its alloys in marine atmospheric environments.
Porous microsphere carriers were prepared using chitosan and polyvinyl alcohol, and loaded with vapor-phase corrosion inhibitors such as benzotriazole, 2-mercaptobenzothiazole and cysteine. The intelligent release of the corrosion inhibitors was achieved by controlling the pore structure through humidity, thereby enhancing the protection of the copper surface.
It achieves controlled release of corrosion inhibitors under different humidity conditions, is environmentally friendly, and has a corrosion inhibition efficiency of over 98%, significantly extending the protection cycle.
Smart Images

Figure CN121016633A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of metal rust prevention, in particular to a humidity response release type loaded gas phase corrosion inhibitor hydrogel microsphere and a preparation method and application thereof. BACKGROUND
[0002] A volatile corrosion inhibitor (VCI) is a kind of corrosion inhibitor prepared through a special synthesis process and compounding. It can be directly gasified at normal temperature and pressure, alone or attached to a suitable carrier. In a sealed environment, the mixed gas containing the VCI rust prevention factor will fill any space gap in the operation unit through its own adjustable continuous volatilization. When the gas encounters a metal surface, it will be adsorbed thereon to form a dense protective film layer with only one or a few molecules thick. The protective film layer can effectively isolate the metal surface from water, oxygen and other harmful atmospheric corrosion factors, and inhibit the occurrence of electrochemical reactions that promote metal corrosion, thereby achieving the best rust prevention effect.
[0003] This technology is particularly suitable for the protection of copper alloys in marine atmospheric environments. In a marine atmospheric corrosion environment, copper and its alloys are easily affected by humidity, temperature and pollutants (such as Cl- and SO2) to cause corrosion, resulting in degradation of the performance of electronic devices and industrial equipment. The volatile corrosion inhibitor (VCI) can automatically volatilize at normal temperature and slowly adsorb on the copper surface in the form of small molecules to form a protective film. Compared with traditional anti-corrosion coatings, VCI can directly reach the fine gaps of the metal surface and form a uniform thin adsorption film to achieve comprehensive protection of the metal copper.
[0004] However, the traditional VCI (such as benzotriazole) has a too fast volatilization rate in a high-temperature and high-humidity environment, resulting in a shortened protection period. To solve this problem, humidity-responsive corrosion carriers have become a research hotspot. SUMMARY
[0005] The application provides a preparation method of a humidity-responsive loaded gas phase corrosion inhibitor hydrogel microsphere, and aims at the deficiencies in the prior art. Green degradable polymer materials such as chitosan (CS) and polyvinyl alcohol (PVA) can be used to prepare porous microsphere carriers through cross-linking, the three-dimensional network structure of which can effectively load VCI molecules, and the intelligent release of VCI can be realized through humidity regulation of the pore structure. In addition, the amino and hydroxyl groups of CS can also form coordination bonds with the copper surface, thereby enhancing the corrosion inhibition effect.
[0006] The preparation method of the humidity-responsive loaded gas phase corrosion inhibitor hydrogel microsphere provided by the application comprises the following steps:
[0007] Preparation of CS / PVA porous microspheres: biodegradable, green and environmentally friendly materials with humidity gate response are selected as the porous core-shell structure microspheres; microfluidic preparation technology and chemical crosslinking means are adopted, the water phase is a mixed solution of water and acetic acid, the oil phase is n-heptane, and the crosslinking agent is selected as glutaraldehyde to obtain an emulsion;
[0008] Load gas phase corrosion inhibitor: the gas phase corrosion inhibitor is loaded into the CS-PVA microspheres by a vacuum negative pressure method; wherein the corrosion inhibitor includes benzotriazole BTA, 2-mercaptobenzothiazole MBT and cysteine CYS.
[0009] The preparation method of the application comprises the following specific steps:
[0010] Dissolve chitosan CS and polyvinyl alcohol PVA powders in deionized water and acetic acid, stand overnight to remove bubbles, and obtain a CS / PVA solution; weigh an equal amount of VCI and add it to the CS / PVA solution and stir, stand for 1-3 h after mixing uniformly, and obtain a CS / PVA@BMC solution water phase;
[0011] Add Span 80 in n-heptane and stir to generate an oil phase; add the drug-loaded CS solution (i.e. the CS / PVA@BMC solution water phase obtained in the previous step) into the oil phase and stir to form a W / O emulsion (i.e. CS microspheres); add a glutaraldehyde solution to further stabilize the CS microspheres, and continue to stir for 2-5 h; then, immerse in a-20 to-30℃ environment for 20-24 h, remove the supernatant after thawing, wash with anhydrous ethanol for 3-5 times, and collect the CS / PVA@BMC microsphere precursor (i.e. drug-loaded hydrogel microspheres);
[0012] Then add 0.5-1.5 M NaOH to the CS / PVA@BMC microspheres collected above, incubate for 1-3 h; then immerse in a corresponding saturated VCI solution for 10-20 h; freeze at a temperature of 4-6℃ for 12-20 h, and freeze-dry to obtain CS / PVA@BMC microspheres, i.e. the humidity-responsive drug-loaded gas phase corrosion inhibitor hydrogel microspheres of the application.
[0013] Chitosan and polyvinyl alcohol are biodegradable and humidity-responsive high molecular materials. As a micro-nano carrier to load VCI, the problem that VCI is directly in contact with corrosive media to cause failure of VCI can be avoided. The corrosion inhibitor can be slowly released into the corrosive medium by a specific stimulus to achieve controllable release of VCI. Chitosan and polyvinyl alcohol contain hydrophilic groups such as amide, amino, carboxyl and hydroxyl in the structure, so they can absorb a large amount of water to swell themselves. In addition, chitosan and polyvinyl alcohol are also effective green corrosion inhibitors. Therefore, CS and PVA are selected for encapsulation to achieve humidity-responsive release of VCI.
[0014] More specifically, the mass concentration of the chitosan CS solution is 0.2% to 2%.
[0015] More specifically, the mass concentration of the polyvinyl alcohol PVA solution is 0.1% to 1%.
[0016] More specifically, the CS / PVA@BMC microspheres have a particle size of 20 to 80 µm.
[0017] Further, the application also provides a gas phase corrosion inhibitor, which is a multi-component composite gas phase corrosion inhibitor and comprises benzotriazole BTA, 2-mercaptobenzothiazole MBT and cysteine CYS.
[0018] Specifically, the equal amount refers to the total mass of the three after preparation and the mass of CS / PVA.
[0019] Specifically, the mass-volume concentration of each component of the multi-component composite gas phase corrosion inhibitor is: 3 to 5 mg / mL of benzotriazole, 5 to 8 mg / mL of 2-mercaptobenzothiazole and 5 to 10 mg / mL of cysteine.
[0020] Specifically, the mass ratio of each component of the multi-component composite gas phase corrosion inhibitor is preferably: benzotriazole: 2-mercaptobenzothiazole: cysteine = 1:1:1.5.
[0021] The technical principle of the application is as follows:
[0022] The gas phase corrosion inhibitor of the application has a synergistic effect of the components. Benzotriazole BTA is a mixed corrosion inhibitor, the polar group of which can be adsorbed on the metal surface and react with the relevant ions in the corrosion medium, and the non-polar group is closely arranged to form a firm corrosion-resistant adsorption film. The active groups such as mercapto groups in the 2-mercaptobenzothiazole MBT molecule have a strong chemical adsorption effect on copper, and the lone pair electrons of the S atoms and N atoms have a chelating effect on copper ions, which has a complexing ability. 2+ Cysteine CYS is a green and non-toxic gas phase corrosion inhibitor, and its molecular structure contains polar groups such as amino groups, carboxyl groups and mercapto groups. These hydrophilic groups interact with the surface of copper metal. The three corrosion inhibitors BTA / MBT / CYS can have a synergistic effect when used together to form a composite corrosion inhibitor. The composite corrosion inhibitor BTA / MBT / CYS is combined with Cu atoms by chemical adsorption method to play a barrier role on the surface of the metal matrix to prevent the invasion of corrosive media. Moreover, the composite corrosion inhibitor BTA / MBT / CYS can form a more compact and more efficient corrosion film than single BTA or MBT or CYS.
[0023] Directly applying the compounded gas phase corrosion inhibitor BTA / MBT / CYS to the corrosion inhibition of copper metal in marine environment cannot make the corrosion inhibitor continuously and efficiently play a role, therefore, the corrosion inhibitor is loaded into the porous micro-nano container, and the corrosion inhibitor is released in a controllable manner through the change of environmental humidity as a stimulation signal. The porous micro-nano container releases the VCI in response to the invading corrosion medium, and then diffuses to the copper metal surface together with the corrosion medium, replaces the water molecules to be adsorbed in advance, and inhibits or delays the corrosion of the Cu metal. The chitosan molecule is rich in hydrophilic groups such as primary amines and hydroxyl groups, therefore, the polyelectrolyte film layer absorbs water and swells in the aqueous solution, providing a channel for the outward transmission of the corrosion inhibitor, and giving the micro-nano container a water-sensitive response. Chitosan also has excellent broad-spectrum antibacterial properties. The positively charged amino groups on the chitosan molecule interact with the negatively charged cell wall to enhance the permeability of the cell wall, causing cell damage, and ultimately causing the death of bacteria. Polyvinyl alcohol PVA has good biocompatibility and can effectively enhance the mechanical properties of the microspheres. The use of chitosan and polyvinyl alcohol PVA in combination not only retains the advantages of both, but also provides a stable matrix for the loaded gas phase corrosion inhibitor. Therefore, the polyelectrolyte CS and PVA are used for encapsulation to realize the controllable release of the gas phase corrosion inhibitor BTA / MBT / CYS under different humidity conditions, and a humidity-responsive porous microsphere corrosion composite material is prepared.
[0024] Beneficial effects: The humidity-responsive release type porous hydrogel microspheres loaded with multiple gas phase corrosion inhibitors of the application have a simple preparation method, good operability and repeatability. The benzotriazole BTA, 2-mercaptobenzothiazole MBT and cysteine CYS are compounded, and have good synergistic effect. Since the encapsulating materials chitosan (CS) and polyvinyl alcohol (PVA) have water molecule sensitivity, the corrosion inhibitor BTA / MBT / CYS can be released in a controllable manner under different humidity conditions, and is green, environmentally friendly, pollution-free, response release efficient and controllable. The corrosion inhibition efficiency for copper metal is up to 98% or more. BRIEF DESCRIPTION OF DRAWINGS
[0025] Figure 1 The synthesis route of the humidity-responsive release type porous hydrogel microspheres loaded with multiple gas phase corrosion inhibitors BMC@CS / PVA in the embodiments of the application is shown in the figure;
[0026] Figure 2 The SEM image of the porous microspheres in the embodiments of the application is shown in the figure;
[0027] Wherein a and b are SEM images of gel microspheres without loading drugs; c and d are overall images of drug-loaded gel microspheres; e is a cross-sectional view; f is a local enlarged view of the pores of the drug-loaded gel microspheres;
[0028] Figure 3 The standard curve of the gas phase corrosion inhibitor BTA / MBT / CYS in the embodiments of the application is shown in the figure;
[0029] Figure 4 The controllable release curve of the gas phase corrosion inhibitor BTA / MBT / CYS over time under different humidity conditions;
[0030] Figure 5 The electrochemical impedance test curve in the embodiment of the application;
[0031] Figure 6 Equivalent circuit fitting data;
[0032] Figure 7 The SEM image comparison of the copper sheet after being hung in the blank and the atmosphere corrosion liquid containing BMC@CS / PVA for 30 days in the embodiment of the application. DETAILED DESCRIPTION
[0033] The technical solutions of the application will be described in detail below through embodiments, but the protection scope of the application is not limited to the embodiments.
[0034] The embodiment provides a humidity response release type loaded gas phase corrosion inhibitor hydrogel microsphere, and a specific process is as follows Figure 1 , and the method specifically comprises the following steps.
[0035] CS and PVA powders are dissolved in deionized water and acetic acid, the mass concentration of the chitosan CS solution is 0.5%, and the mass concentration of the polyvinyl alcohol PVA solution is 0.5%. After being left overnight to remove bubbles, an equal amount of VCI is weighed and added to the CS / PVA solution and stirred, and after being uniformly mixed, the solution is left to stand for 1.5 h. Span 80 is added to n-heptane to generate an oil phase by stirring. The drug-loaded CS solution is added to the oil phase to form a W / O emulsion by stirring. Glutaraldehyde solution is further added to stabilize the CS microspheres, and the stirring is continued for 4 h. Subsequently, the solution is placed in an environment of-20 to-30 DEG C and left to soak overnight. After being thawed, the supernatant is removed, and the solution is washed with anhydrous ethanol for 5 times. The CS / PVA@BMC microsphere precursor is collected. Then, 0.5M NaOH is added to the microsphere precursor, and the solution is incubated for 3 h. The solution is immersed in the corresponding saturated VCI solution for 10 h. The solution is placed in a refrigerator and frozen for 20 h. The obtained microspheres are freeze-dried to obtain the CS / PVA@BMC microspheres. That is, the humidity response type loaded gas phase corrosion inhibitor hydrogel microsphere is obtained.
[0036] The VCI in the above step is specifically benzotriazole: 2-mercaptobenzothiazole: cysteine = 1:1:1.5. The equal amount means that the total mass of the three after preparation is weighed and is equivalent to the mass of CS / PVA.
[0037] Humidity response release of the gas phase corrosion inhibitor:
[0038] The release of the corrosion inhibitor BTA / MBT / CYS under different humidity conditions was tested using a UV-visible spectrophotometer model U-3900 produced by a Japanese company.
[0039] The concentration gradient of the compounded BTA / MBT / CYS standard solution was configured to be 0 mg / L, 2 mg / L, 5 mg / L, 8 mg / L, 10 mg / L, and 12 mg / L, and the absorbance of BTA / MBT / CYS at the maximum wavelength was measured by a UV-visible spectrophotometer (UV-vis). Each concentration was tested in triplicate, and the average value was taken. The relationship between the solution concentration and the absorbance was obtained by drawing and fitting the BTA / MBT / CYS standard curve.
[0040] A solution prepared from 0.1 g / L NaCl, 0.1 g / L NaHCO3, and 0.1 g / L Na2SO4 with a humidity of 33%, 55%, 75%, and 84% was selected as the release medium to simulate the corrosion environment. 30 mg of the CS / PVA@BMC microspheres prepared in the above experiment (hereinafter referred to as CS / PVA@BMC) were added to 200 mL of a closed environment with different humidity, and 3 mL of the solution was taken from the supernatant to measure the absorbance within a specified time. The cumulative release amount of BTA / MBT / CYS was calculated by comparing with the fitting equation of BTA / MBT / CYS, and the corresponding humidity-responsive controlled release curve was drawn.
[0041] Electrochemical test:
[0042] An electrochemical workstation (Autolab PGSTAT302N) was used to perform electrochemical impedance spectroscopy (EIS) test on copper sheets using a conventional three-electrode system. The working electrode was a copper block with an exposed area of 1×1 cm 2 , the counter electrode was a platinum sheet, and the reference electrode was a saturated calomel electrode. It was immersed in an atmospheric corrosion simulation solution, and the electrochemical impedance spectroscopy (EIS) test was performed on the 30th day after immersion. First, the open circuit potential test was performed for 30 min, and a sinusoidal wave of ±5 mV was applied as the alternating current signal. The scan frequency range was 10 -2 ~10 5 Hz, and the experimental data was fitted by ZsimDemo fitting software. The calculation formula of the electrochemical impedance corrosion efficiency is:
[0043]
[0044] Surface morphology observation:
[0045] The CS / PVA
[0046] Micro-morphology of the BMC and the corrosion morphology of the copper sample surface.
[0047] Micro-morphology analysis of CS / PVA@BMC:
[0048] Figure 2 (a) and (b) are SEM images of drug-free gel microspheres, which can be seen to have porous characteristics. (c) and (d) are whole images of drug-loaded gel microspheres, and the pores are larger after drug loading than before drug loading; (e) is a cross-sectional image of drug-loaded gel microspheres, and the porous characteristics are still intact after drug loading; (f) is a local enlarged image of the pores of the drug-loaded gel microspheres, and it can be seen from the image that the loading rate of the gas phase corrosion inhibitor is high, and the drug loading rate is more than 30% according to the ultraviolet absorbance calculation.
[0049] Humidity-controlled release analysis of CS / PVA@BMC:
[0050] The standard curve of BTA / MBT / CYS is shown in Figure 3 , and the R 2 of the fitting equation is 0.9988. This fitting equation can provide a calculation standard for the subsequent control release of BTA / MBT / CYS. Figure 4 The results show that BTA / MBT / CYS is successfully released under different humidity conditions. And with the increase of humidity, the release rate gradually increases. When the release time is 7 days, the release amount is about 45%; when the release time reaches 30 days, the release amount is about 80%. In the blank control, without using the carrier, the release amount after 7 days of soaking is 80%, and it approaches 100% on the 10th day. The comparison results show that after the gas phase corrosion inhibitor is loaded with the carrier, the overall release proportion decreases and the release time increases, indicating that this microsphere carrier can provide long-term stable release of the gas phase corrosion inhibitor and better protection for the metal.
[0051] Electrochemical impedance spectroscopy test analysis:
[0052] Figure 5 The impedance spectroscopy test curve is shown in the figure, and the results show a semicircular ring, which is due to the roughness and unevenness of the surface of the working electrode. This behavior can occur at the frequency depression of the interfacial impedance, and the diameter is proportional to the corrosion inhibition efficiency, indicating that the inhibition of low carbon steel is mainly through the coverage of the metal surface and the charge transfer mechanism. Figure 6 The fitting circuit diagram is shown in the figure. The calculated corrosion inhibition efficiency of the composite gas phase corrosion inhibitor CYS / MBT / BTA is 89.6%, and the corrosion inhibition efficiency of the loaded CS / PVA@BMC is 95.9%.
[0053]
[0054] Surface morphology analysis:
[0055] Figure 7 The SEM photos of copper sheets immersed in blank and CS / PVA@BMC-containing atmospheric corrosion simulation solution for 4 weeks are shown. The surface of the blank control group is rough and has many cracks after immersion. Large pieces of corrosion products with network cracks can be clearly observed Figure 7 a). It indicates that without corrosion inhibitor, the copper sheet is easy to be eroded by corrosive particles (H2O, Cl - ). The metal surface is severely corroded. While the copper surface immersed in the corrosion solution containing CS / PVA@BMC has no large amount of rust products. The surface morphology of the copper is clean and neat except for the initial scratch, the corrosion degree is lighter Figure 7 b), and the surface is smooth and flat, showing excellent corrosion resistance. The SEM results are in good agreement with the previous EIS results.
[0056] The above description is only the preferred embodiment of the present application, and does not limit the present application in any form. Although the present application has been disclosed as above with the preferred embodiment, it is not intended to limit the present application. Any person skilled in the art can make some changes or modifications to the above disclosed technical content to make equivalent embodiments with equivalent changes, without departing from the technical solution of the present application. Any modification, equivalent change and modification of the above embodiments made in accordance with the technical essence of the present application shall still fall within the scope of the technical solution of the present application.
Claims
1. A method for preparing a humidity-responsive hydrogel microsphere loaded with a vapor phase corrosion inhibitor, characterized in that, Includes the following steps: Chitosan (CS) and polyvinyl alcohol (PVA) powders were dissolved in deionized water and acetic acid, and allowed to stand overnight to remove bubbles, resulting in a CS / PVA solution. An equal amount of VCI was weighed and added to the CS / PVA solution and stirred. After mixing evenly, the solution was allowed to stand for 1–3 hours to obtain the aqueous phase of the CS / PVA@BMC solution. Span 80 was added to n-heptane and stirred to generate an oil phase; the drug-loaded CS solution was added to the oil phase and stirred to form a W / O emulsion; glutaraldehyde solution was added to further stabilize the CS microspheres, and stirring was continued for 2-5 hours; then, the microspheres were placed in an environment of -20 to -30°C for 20-24 hours, and after thawing, the supernatant was removed, and the microspheres were washed 3-5 times with anhydrous ethanol to collect the CS / PVA@BMC microsphere precursor. Then, 0.5–1.5 M NaOH was added to the collected microsphere precursors and incubated for 1–3 h; then, the microspheres were immersed in the corresponding saturated VCI solution for 10–20 h; and then, they were frozen at 4–6 °C for 12–20 h and freeze-dried to obtain CS / PVA@BMC microspheres, which are the humidity-responsive hydrogel microspheres with supported vapor phase corrosion inhibitors described in this invention.
2. The preparation method according to claim 1, characterized in that, The mass concentration of the chitosan CS solution is 0.2% to 2%.
3. The preparation method according to claim 1, characterized in that, The mass concentration of the polyvinyl alcohol (PVA) solution is 0.1% to 1%.
4. The preparation method according to claim 1, characterized in that, The VCI is a multi-component composite vapor phase corrosion inhibitor containing benzotriazole (BTA), 2-mercaptobenzothiazole (MBT), and cysteine (CYS).
5. The preparation method according to claim 1, characterized in that, The phrase "weighing in equal quantities" means that the total mass of the three components after preparation is equal to the mass of CS / PVA.
6. The preparation method according to claim 1, characterized in that, The mass-volume concentrations of each component in the multi-component composite vapor phase corrosion inhibitor are: 3–5 mg / mL benzotriazole, 5–8 mg / mL 2-mercaptobenzothiazole, and 5–10 mg / mL cysteine.
7. The humidity-responsive hydrogel microspheres loaded with vapor phase corrosion inhibitor obtained by the preparation method of claim 1.
8. The hydrogel microspheres according to claim 7, characterized in that, The particle size is 20–80 μm.
9. The application of the humidity-responsive hydrogel microspheres loaded with vapor phase corrosion inhibitor as described in claim 7.
10. The application according to claim 9, characterized in that, For corrosion resistance of copper metal.